2005
DOI: 10.1007/s11149-005-3955-1
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Termination: What is the “Right” Charge?*

Abstract: The regulation of fixed-to-mobile (F2M) termination charges has become increasingly important in Europe, Australia, and New Zealand under the Calling Party Pays principle. In the absence of any regulation, mobile operators have an incentive to set F2M termination charges “too high”. We show that the setting of the optimal F2M termination charges depends on the significance of network externalities, the intensity of competition in the mobile sector, and the distribution of customer preferences. We also discuss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 17 publications
0
17
0
2
Order By: Relevance
“…68 Now, an increase in a F above marginal cost increases the pro…ts of mobile network, some or all of which is passed on to mobile subscribers via the waterbed e¤ect, but simultaneously reduces the utility received by the mobile network's subscribers (10)), but also optimal for the mobile network's subscribers. Thus, we can no longer say that setting a …x e d -t o -m o b i l e termination rate above marginal cost, or even above zero, bene…ts mobile subscribers considered in isolation.…”
Section: Wa T E R B E D S and Relaxing Competition For Market Sharementioning
confidence: 99%
See 1 more Smart Citation
“…68 Now, an increase in a F above marginal cost increases the pro…ts of mobile network, some or all of which is passed on to mobile subscribers via the waterbed e¤ect, but simultaneously reduces the utility received by the mobile network's subscribers (10)), but also optimal for the mobile network's subscribers. Thus, we can no longer say that setting a …x e d -t o -m o b i l e termination rate above marginal cost, or even above zero, bene…ts mobile subscribers considered in isolation.…”
Section: Wa T E R B E D S and Relaxing Competition For Market Sharementioning
confidence: 99%
“…77 Armstrong (2002), Wright (2002a) and Valletti and Houpis (2005) also found that the welfare-maximizing …x e d -t o -m o b i l e termination charge is above cost when there is scope for market expansion. These models did not allow for mobile-to-mobile calls, however.…”
mentioning
confidence: 99%
“…Armstrong and Wright (2009a) conclude that socially optimal MTRs should exceed the marginal cost of termination, and that the …xed-to-mobile and mobile-to-mobile rates should be set at di¤erent levels, if feasible. 52 Armstrong (2002), Wright (2002) and Valletti and Houpis (2005) also found that the welfaremaximizing …xed-to-mobile termination charge is above cost when there is scope for market expansion.…”
Section: Long-run E¤ectsmentioning
confidence: 99%
“…60 We have used this information to estimate the equivalent level annuity which would match these e¢ ciency gains, i.e. a constant per annum net saving which delivers the same NPV as the variable pro…le of savings described above.…”
Section: Subscription Feesmentioning
confidence: 99%
“…45 off-peak calls. 50 Pre-pay packages also tend to offer generous or unlimited minute allowances for both on-net and off-peak, off-net calls. 51 The situation in Hong Kong and Singapore is very different.…”
Section: International Experience With Bill and Keepmentioning
confidence: 99%